The Role of Ethylene in Plant Responses to K+ Deficiency - Schachtman, Daniel P. (Frontiers in Plant Science, 2015)
Potassium is an essential macronutrient that is involved in regulating turgor, in driving plant growth, and in modulating enzyme activation. The changes in root morphology, root function, as well as cellular and molecular responses to low potassium conditions have been studied in the model plant Arabidopsis and in other plant species. In Arabidopsis ethylene plays a key role in roots in the transduction of the low potassium signal, which results in altered root function and growth. The first clues regarding the role of ethylene were detected through transcriptional profiling experiments showing changes in the expression of genes related to ethylene biosynthesis. Later it was shown that ethylene plays a foundational early role in the many responses observed in Arabidopsis. One of the most striking findings is the link between ethylene and reactive oxygen species (ROS) production, which is part of the signal transduction pathway in K+ deprived plants. This mini-review will summarize what is known about the role ethylene plays in response to low potassium in Arabidopsis and other plant species.